Pengaruh Biaya Operasional, Pinjaman Perusahaan, Ukuran Perusahaan, dan Struktur Modal Terhadap Kinerja Keuangan Dimasa Pandemi Covid-19 (Studi Kasus pada PT. Usada Pak Oles): (Studi Kasus pada PT. Usada Pak Oles) - Putu Puspita Damayanti; Ni Luh Gede Erni Sulindawati (Universitas Pendidikan Ganesha, 2022)
This study aims to determine and analyze the effect of operating costs, company credit, company size, and capital structure on financial performance during the pandemic covid-19. The independent variables in this study are operational costs, company credit, comany size, and capital dtructure and the dependent variabel is financial performance. The type of data usedis secondary data in the form of scientific journals and annual report of the companies. Data collection method using the documentation method. Data analyis techniques using multiplelinear analysis techniques. The results of the study partially showed that operting expenses, corporate loans and capital structures had a positive and significant effect on financial performance, while the size of the company had a negative and significant effect on financial performance.